2000
DOI: 10.1107/s0021889899012625
|View full text |Cite
|
Sign up to set email alerts
|

Study of thermal behaviour of 30Li2O·70TeO2glass by X-ray dynamic observation

Abstract: The thermal behaviour of a 30Li2O·70TeO2 glass was studied by use of an in situ high‐temperature X‐ray diffractometer equipped with a position‐sensitive detector (PSD). The dynamical structural changes were also observed by differential thermal analysis (DTA) and differential scanning calorimetry (DSC) measurements. Differences and contradictions exist in previous studies related to the phase relation at high temperature, including the process of phase change. It is found that in the exothermic process after a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The technological applications of these glasses require a profound comprehension of several properties. In this context, structural [3][4][5] and electrical properties [6] were investigated in order to understand all important aspects of these glasses. Nowadays, the technological use of tellurium-based glasses is a reality that justifies progressive investigations on optical, structural and electrical properties [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The technological applications of these glasses require a profound comprehension of several properties. In this context, structural [3][4][5] and electrical properties [6] were investigated in order to understand all important aspects of these glasses. Nowadays, the technological use of tellurium-based glasses is a reality that justifies progressive investigations on optical, structural and electrical properties [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…When the glass crystallizes, the α-TeO 2 and the ZnTeO 3 phases were found to crystallize first, followed by the crystallization of the Zn 2 Te 3 O 8 phase. Nukui et al 8) reported that the predominant crystallization of the ZnTeO 3 phase from the glass attributes to the inhmogeneity of the glass structure, even though the phase is generally unexpected. While dur- ing the cooling process from the melt, the α-TeO 2 phase was found to crystallize first, followed by the crystallization of the Zn 2 Te 3 O 8 phase.…”
Section: Phase Relationmentioning
confidence: 99%
“…In situ observations are useful in directly obtaining data of thermal behavior. 8) Furthermore, the X-ray system can be used to produce rapid measurements, and thus, direct comparison can be made with DTA results, with respect to structural changes and thermal reactions. The crystallization behavior of the 20ZnO·80TeO 2 glass will be discussed in terms of the Temperature-Time-Transfer (T-T-T) diagram.…”
Section: Introductionmentioning
confidence: 99%